PENGARUH BUDAYA LITERASI TERHADAP KEMAMPUAN MENYELESAIKAN SOAL BAHASA INDONESIA TIPE HOTS SISWA KELAS 3 DI SDN PEJATEN BARAT 08 JAKARTA - Prijayanti, Irbiani; Mulyawati, Ima (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2023)
Students' ability to solve HOTS-type Indonesian questions is still weak. This is due to a literacy culture that has not grown in students and teachers also have not familiarized students with solving HOTS-type questions. The purpose of research in this article to know determine the effect of literacy culture on the ability to solve HOTS-type Indonesian questions in 3rd-grade students at SDN Pejaten Barat 08 Jakarta in the 2022/2023 academic year. This study used quantitative correlational research with a saturated sample of 46 students. The study uses descriptive statistical data analysis techniques and inferential. The results of the research is tcount literacy culture of 3,993 ≥ 1,677 ttable with Sig value. 0.000 < 0.005, and the R-Squared is 0.266 or 26.6%. The concllusion is literacy culture has a significantly positively affects on the ability to solve HOTS-type Indonesian questions in 3rd-grade students at SDN Pejaten Barat 08 Jakarta for the 2022/2023 academic year.